2018
DOI: 10.3390/rs10040646
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heavy Precipitation Simulated by the WRF Model Using 4D-Var Data Assimilation with TRMM 3B42 and GPM IMERG over the Huaihe River Basin, China

Abstract: To obtain independent, consecutive, and high-resolution precipitation data, the four-dimensional variational (4D-Var) method was applied to directly assimilate satellite precipitation products into the Weather Research and Forecasting (WRF) model. The precipitation products of the Tropical Rainfall Measuring Mission 3B42 (TRMM 3B42) and its successor, the Integrated Multi-satellitE Retrievals for Global Precipitation Measurement (GPM IMERG) were assimilated in this study. Two heavy precipitation events that oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 69 publications
0
23
0
1
Order By: Relevance
“…The GPM IMERG was selected as the observation operator because of its recent release, wide coverage, free download and high accuracy [70]. Moreover, the feasibility of assimilating the GPM IMERG into the WRF model has been demonstrated in Yi et al [18]. The GPM IMERG was accumulated into 6 h values and assimilated into the WRF 4D-Var system to improve the initial condition at every day 00 UTC.…”
Section: Nwp-predicted Precipitationmentioning
confidence: 99%
“…The GPM IMERG was selected as the observation operator because of its recent release, wide coverage, free download and high accuracy [70]. Moreover, the feasibility of assimilating the GPM IMERG into the WRF model has been demonstrated in Yi et al [18]. The GPM IMERG was accumulated into 6 h values and assimilated into the WRF 4D-Var system to improve the initial condition at every day 00 UTC.…”
Section: Nwp-predicted Precipitationmentioning
confidence: 99%
“…However, gauges in mountainous regions are often sparse, uneven, and sometimes not available [2,6,7]. Thus, in the applications that need high spatiotemporal resolution precipitation data, such as flood disaster forecasts, gauge data are often not sufficient [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…DA-IMERG experiment was directly assimilated IMERG precipitation products utilizing 4D-Var. The IMERG precipitation product was applied as observation operators, which was collected and accumulated every 6h for assimilating into the DA-IMERG experiment [16]. For comparison purposes, The DA-CONV was based on the assimilation of conventional observations (surface observational weather data (ds461.0) and upper air observational weather data (ds351.0)) from the Research Data Archive at the National Center for Atmospheric Research (https://rda.ucar.edu/datasets/).…”
Section: Experiments Designmentioning
confidence: 99%
“…However, the accuracy of precipitation simulated by WRF with 4D-Var depends on the assimilation data. Yi et al [16] reported that WRF precipitation assimilated with GPM IMERG outperformed that with TRMM-3B42.…”
Section: Introductionmentioning
confidence: 99%